Survival and complications of implant-supported cantilever fixed dental prostheses with zirconia and metal frameworks: a retrospective cohort study - Horsch, Laura; Kronsteiner, Dorothea; Rammelsberg, Peter (Clinical implant dentistry and related research, 2022)
Background Current evidence about long-term survival of all-ceramic implant-supported cantilever fixed dental prostheses (cFDP) is limited. Purpose To evaluate the survival and complication rates of all-ceramic and metal-ceramic implant-supported cFDPs located in anterior and posterior sites, under consideration of risk factors. Methods of study The retrospective analysis compared an experimental group (75 implant-supported cFDPs among 48 patients [mean age 60.47 ± 9.25 years; 21 men]; mean observation period 3.56 years) with a control group (300 implant-supported non-cantilever FDPs [ncFDP] among 241 patients [mean age 62.85 ± 10.72 years; 109 men]; mean observation period 7.25 years). Kaplan-Meier estimates were used to describe the long-term survival and success of both groups. Log-rank tests were used for group comparisons. Mixed-effects Cox proportional hazards regression models were used to examine the effects of restoration- and site-specific risk factors. A random intercept was included in the models to take multiple FDPs per patient into account. Results Five-year cumulative survival until loss of restoration was 97.1% (95% confidence interval [CI] 0.93-1.00) for cFDPs and 97.0% (95% CI 0.95-0.99) for ncFDPs. Ten-year survival was 93.7% (95% CI 0.86-1.00) for cFDPs and 92.8% (95% CI 0.87-0.98) for ncFDPs, no difference between the survival curves of these groups was observed. Success differed between cFDPs and ncFDPs (pLog = 0.002), zirconia and metal frameworks (pLog < 0.001), and provisional and definitive cements (pLog = 0.025). The effects of the variables “framework material” and “attachment method” were confirmed in a mixed-effects Cox regression model. Loss of retention was the predominant complication for both cFDPs and ncFDPs and usually affected provisionally cemented FDPs. Conclusions cFDPs do not differ from ncFDPs with regard to long-term failure, whereas additional complications were higher for cFDPs. Fewer complications were observed for zirconia frameworks without occlusal veneers and definitive cemented FDPs. Clinical trial registration: the trial has no registration number because it commenced before January 31, 2017.
First published: 04 August 2022
Gesehen am 09.12.2022